Analisis Faktor Yang Mempengaruhi Pembentukan Serumen Obsturan Pada Pasien Rawat Jalan Di Poliklinik THT RSUD Dr. Soeroto Ngawi Tahun 2016 - Melinda, Novendra Maya; , Dr. Arne Laksmiasanti, Sp.THT-KL., M.Kes; , Dr. Erna Herawati, Sp.K.J (2017)
Factors influencing the high incidence of cerumen obsturan already known theoretically, but has not been widely studied. This study aims to identify and prove the factors that influence the formation of cerumen obsturan. This study aimed to determine what are the risk factors of cerumen obsturan at the outpatient clinic of dr. Soeroto Ngawi. The study was observational analytic with design. Cross-sectional sample of all outpatients who visited the clinic dr. Soeroto Ngawi dated 1 November to 1 December 2016 meet the criteria for inclusion and exclusion with method. Consecutive sampling samples were examined using an otoscope tool on both ears. Factors affecting the formation of cerumen obsturan assessed through several questions posed in the questionnaire. The incidence of cerumen obsturan as much as 72% (72 patients) of the 100 patients studied. The distribution of the sexes in this study consisted of 33 male patients and 67 female patients with cerumendistribution obsturan by 23 (69.7%) patients were male and 49 (73.1%) patients were female. The results of comparative Chi-square test and logistic regression between the formation of cerumen obsturan by sex, age, body mass index (BMI), history of ear pain and a job not found a significant relationship. After being tested using logistic regression, ear cleaning behavior significantly associated with the occurrence of cerumen obsturan. There were no significant association between earwax obsturan by sex, age, body mass index (BMI), history of ear pain, work. Significant relationships found between the incidence of cerumen obsturan behavior ear cleaning. Keywords: factors of influence, cerumen obsturan